QUALITY OF LIFE AND VOICE IN TOTALLY LARYNGECTOMIZED PATIENTS: LITERATURE REVIEW - Silva Ramos, Giovanna (Health and Society, 2022)
Objective: To carry out a literature review on quality of life and voice in total laryngectomized patients. Methods: The present study consists of a bibliographic review, with articles located in the SciELO (Scientific Electronic Library Online) and VHL (Virtual Health Library) databases, in which 05 articles were selected between the years 2009 to 2019, all with direct relationship with the proposed theme. Conclusion: It was possible to conclude that the results through the protocols are important for the evaluation and treatment of individuals who underwent total laryngectomy, since speech was the most significant domain, directly interfering with the communication and quality of life of patients.